A Comprehensive Review of Sequencing and Combination Strategies of Targeted Agents in Metastatic Colorectal Cancer. (11th October 2017) - Ciombor, Kristen K.; Bekaii‐Saab, Tanios
Abstract : : The emergence of targeted therapies for the treatment of metastatic colorectal cancer (mCRC) has considerably improved survival, but has also resulted in a dilemma of identifying the optimal sequence and combination of various agents in the mCRC treatment landscape. A number of cytotoxic agents, including irinotecan, oxaliplatin, 5‐fluorouracil, capecitabine, and TAS‐102, are available for treatment of mCRC. Additionally, whereas patients harboring rat sarcoma viral oncogene homolog ( RAS )–wild type mCRC can be treated with the anti‐epidermal growth factor receptor antibodies cetuximab and panitumumab or antiangiogenic agents (bevacizumab, ziv‐aflibercept, and ramucirumab), patients with RAS ‐mutant mCRC are limited to antiangiogenic agents as biologic options. Regorafenib, a multikinase inhibitor, can be used in both RAS subgroups. As such, the recommended sequence of therapies that should be received by each subgroup must also be considered separately. This review provides an overview of recent clinical data for approved and investigational targeted therapies that have been studied across different mCRC treatment lines and patient subgroups. It also examines emerging trends in the treatment landscape for mCRC, including treatment with immune checkpoint inhibitors and the utilization of genomic profiling. Implications for Practice: Currently, there are no established guidelines for optimal sequencing of cytotoxic or targeted agents in metastatic colorectal cancer (mCRC). This review provides a snapshot of the current mCRC treatment paradigm and examines the latest clinical data that support the utilization of several targeted agents alone or in combination with backbone chemotherapy across different lines of treatment and patient populations, highlighting recommendations for their usage. Recent advances in the treatment landscape are also summarized, including genomic profiling and preliminary results with immune checkpoint inhibitors. Abstract : This article summarizes the current treatment landscape for metastatic colorectal cancer, reviews the clinical data supporting the roles for targeted therapies in treatment sequencing, examines investigational treatments for third‐line metastatic colorectal cancer, and reviews emerging trends in therapeutic strategies and molecular testing.